PERSEPSI ORANG TUA TERHADAP DAMPAK PENGGUNAAN GADGET PADA ANAK USIA 11 SAMPAI 13 TAHUN - Anita Amelia Ole; Gabriella Alleid Dian Baureh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The use of gadgets among children aged 11-13 has increased as technology has developed. While gadgets support learning and communication, they can also negatively affect child development if not properly controlled. This study examines parents' perceptions of the impact of gadget use on children aged 11–13. It uses a qualitative case study approach involving 4 parents of children aged 11- 13 from different educational and occupational backgrounds. Data were collected through structured interviews and analyzed descriptively. The results showed that parents viewed gadgets as helpful for school assignments, increasing knowledge, and facilitating communication. However, excessive use can cause children to become more emotional and easily angered, reduce concentration in studies, limit social interaction, frequently cause conflicts with parents, and affect health, such as eye strain and headaches. Therefore, parents need to supervise their children by limiting gadget use. They should also communicate well with their children to maximize gadget benefits and minimize negative impacts. Parents play an important role in shaping healthy gadget habits in children.